Formation of Nicknames and Study by Uzbeki Linguists - Karimboyeva Manzura Dilmuratovna (Genius Journals, 2022)
This article provides information about nicknames that are being studied as an anthroponymic unit in Uzbek linguistics. The opinions of linguists about nicknames are presented. Considerations have been made regarding the distinction between nicknames and names.
Keywords: Uzbek linguistics; anthroponymy; onomastics